2014
DOI: 10.1016/j.bandl.2014.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual integration for speech during mid-childhood: Electrophysiological evidence

Abstract: Previous studies have demonstrated that the presence of visual speech cues reduces the amplitude and latency of the N1 and P2 event-related potential (ERP) components elicited by speech stimuli. However, the developmental trajectory of this effect is not yet fully mapped. We examined ERP responses to auditory, visual, and audiovisual speech in two groups of school-age children (7–8-year-olds and 10–11-year-olds) and in adults. Audiovisual speech led to the attenuation of the N1 and P2 components in all groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 85 publications
1
14
0
Order By: Relevance
“…Any work that did not include GAs for auditory speech as well as for AV(−V), or did not allow those conditions to be estimated, was excluded as well (Knowland, Mercure, Karmiloff‐Smith, Dick, & Thomas, ; Liu, Lin, Gao, & Dang, ; Magnée, de Gelder, van Engeland, & Kemner, ; Winkler, Horvath, Weisz, & Trejo, ), because study‐specific parameters that have an overall effect on the GAs can only be factored out when considering both A and AV(−V). For reasons of homogeneity, studies that did not involve adults (e.g., Megnin et al, ) or tested elderly participants (e.g., Musacchia, Arum, Nicol, Garstecki, & Kraus, ) were also excluded, as the amplitude, morphology, and topographic distribution of the N1/P2 complex changes over developmental time (e.g., Anderer, Semlitsch, & Saletu, ; Kaganovich & Schumaker, ; Tonnquist‐Uhlen, Borg, & Spens, ; Wunderlich, Cone‐Wesson, & Shepherd, ). Finally, to ensure that data estimates were taken from comparable electrode sites, studies that did not plot GAs for the critical conditions at mid(fronto)central electrode sites (where the N1 and P2 are maximized) were not considered (Altieri & Wenger, ; Stevenson et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Any work that did not include GAs for auditory speech as well as for AV(−V), or did not allow those conditions to be estimated, was excluded as well (Knowland, Mercure, Karmiloff‐Smith, Dick, & Thomas, ; Liu, Lin, Gao, & Dang, ; Magnée, de Gelder, van Engeland, & Kemner, ; Winkler, Horvath, Weisz, & Trejo, ), because study‐specific parameters that have an overall effect on the GAs can only be factored out when considering both A and AV(−V). For reasons of homogeneity, studies that did not involve adults (e.g., Megnin et al, ) or tested elderly participants (e.g., Musacchia, Arum, Nicol, Garstecki, & Kraus, ) were also excluded, as the amplitude, morphology, and topographic distribution of the N1/P2 complex changes over developmental time (e.g., Anderer, Semlitsch, & Saletu, ; Kaganovich & Schumaker, ; Tonnquist‐Uhlen, Borg, & Spens, ; Wunderlich, Cone‐Wesson, & Shepherd, ). Finally, to ensure that data estimates were taken from comparable electrode sites, studies that did not plot GAs for the critical conditions at mid(fronto)central electrode sites (where the N1 and P2 are maximized) were not considered (Altieri & Wenger, ; Stevenson et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Clicking on any point in the figure will generate its estimated coordinates that can be saved for offline analyses. As can be seen in Table 1, the majority of the work did not include AV2V GAs, but whenever AV and V-only were provided (Besle, Fort, Delpuech, & Giard, 2004;Frtusova et al, 2013;Gilbert et al, 2012;Huhn et al, 2009;Kaganovich & Schumaker, 2014;Klucharev et al, 2003;Pilling, 2009;van Wassenhove et al, 2005), AV2V values were computed by subtracting V-only from AV. EasyNData measures (that were taken by the author) are, in general, quite accurate as described in the supporting documentation (http://puwer.web.cern.ch/puwer/Easy-NData/paper.pdf).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For children across this age group, P2 had a shorter latency when visual speech was present, and adults had an additional N1 latency facilitation. Kaganovich and Schumaker (2014) studied two groups of school-age children (7-8-year-olds and 10-11-year-olds) as well as adults, using audiovisual syllables as stimuli with an equal probability of presentation. They found a similar latency facilitation as Knowland et al (2014), that is, that the P2 latency was shorter for audiovisual than auditory speech in all groups.…”
Section: Neural Change Detection Responses To Speech In Childrenmentioning
confidence: 99%
“…More specifically, we asked at which point in time brain responses of individuals who are better detectors of asynchrony (i.e., good performers) differ from brain responses of those individuals who are worse detectors of asynchrony (i.e., poor performers), with the expectation that the outcome of this comparison would be informative as to the perceptual and cognitive processes that underlie individual variability in sensitivity to temporal asynchrony. Earlier ERP studies of audiovisual integration reported the attenuation of the auditory N1 and/or P2 component to audiovisual as compared to the sum of auditory only and visual only stimuli (Baart, Stekelenburg, & Vroomen, 2014; Besle, Fort, Delpuech, & Giard, 2004; Kaganovich & Schumaker, 2014; Knowland, Mercure, Karmiloff-Smith, Dick, & Thomas, 2014; Stekelenburg & Vroomen, 2007; van Wassenhove, Grant, & Poeppel, 2005). However, given significant design differences between the SJT and the above studies, focusing on just N1 and P2 in our analyses was not justifiable.…”
Section: Introductionmentioning
confidence: 99%